SEISMIC ATTENUATION FROM VSP DATA IN METHANE HYDRATE-BEARING SEDIMENTS - Matsushima J. (My University, 2007)
Recent seismic surveys have shown that the presence of methane hydrate (MH) in sediments has significant influence on seismic attenuation. I have used vertical seismic profile (VSP) data from a Nankai Trough exploratory well, offshore Tokai in central Japan, to estimate compressional attenuation in MH-bearing sediments at seismic frequencies of 30–110Hz. The use of two different measurement methods (spectral ratio and centroid frequency shift methods) provides an opportunity to validate the attenuation measurements. The sensitivity of attenuation analyses to different depth intervals, borehole irregularities, and different frequency ranges was also examined to validate the stability of attenuation estimation. I found no significant compressional attenuation in MH-bearing sediments at seismic frequencies. Macroscopically, the peaks of highest attenuation in the seismic frequency range correspond to low-saturation gas zones. In contrast, high compressional attenuation zones in the sonic frequency range (10–20kHz) are associated with the presence of methane hydrates at the same well locations. Thus, this study demonstrated the frequency-dependence of attenuation in MH-bearing sediments; MH-bearing sediments cause attenuation in the sonic frequency range rather than the seismic frequency range. As a possible reason why seismic frequencies in the 30–110Hz range were not affected in MH-bearing sediments, I point out the effect of thin layering of MH-bearing zones. © 2007, CSIRO. All rights reserved.